(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2016)
The practice of immersion in burn patient has been abandoned in many parts of the world but in Brazil it is still common. The aim of this study was to ascertain if balneotherapy is a risk factor for Pseudomonas aeruginosa colonization in thermally injured patients. Eighteen patients from a Burn Center were studied for 14 weeks for Pseudomonas aeruginosa. Samples were collected by swabbing the exudate of wounds, before and after giving bath to the patients and from balneotherapy table. Pulsed-field gel electrophoresis was used to determine bacterial genetic relatedness. Thirty-seven P. aeruginosa isolates were detected from 292 swabs collected from patients' burn surface area and from the balneotherapy table. Profile analysis of P. aeruginosa DNA fragmentation showed 10 clones among the 37 strains analyzed. Type A is the most prevalent clone, with 23 strains distributed into eight subtypes. These were present in the swabs collected, before and after the patients' bath, from the surface of the bath table, suggesting that there was cross-contamination between the patients in different ways. This work demonstrates that balneotherapy is a risk factor in the Burn Center studied, because the same clone was found among P. aeruginosa isolates collected at various points and times.